Under‐Served Groups and Myalgic Encephalomyelitis Research Workshop; Multiple Barriers to Effective Healthcare, Research and Public Participation - Monica Jane Bolton; Carolyn A. Chew‐Graham; Harm vanMarwijk (Health Expectations)
ABSTRACT Public involvement in research and other initiatives for myalgic encephalomyelitis (ME) (also known as chronic fatigue syndrome) has been crucial in raising awareness of the disease and exposing inadequate healthcare and research funding. An online workshop on ME research and under‐served groups took place in July 2024, organised by the first author, a person with ME. The workshop illustrated very low prevalence and thus barriers to healthcare as well as limited research in people from under‐served groups, who appear doubly disadvantaged by their illness and their socioeconomic and/or ethnic background. Three particular challenges were suggested to account for these disparities: stigma, lack of knowledge (within the general public, amongst healthcare workers and policy makers) and lack of power, particularly in improving current deficiencies. These challenges appear to be significant factors in preventing increased research funding and healthcare provision for ME generally. We call on government and funding bodies to provide strategic funding to correct years of systemic under‐resourcing. Widespread educational initiatives should alert healthcare workers and the public to the possible presence of ME in people from under‐served groups. Research is now urgently needed to understand the barriers to diagnosis and care for people with this illness, particularly for those from under‐served groups. Patient or Public Contribution The first author, a person with ME, was a patient representative on the government‐initiated Research Working Group. As a result, she organised a series of online workshops on ME clinical research, attended by researchers, clinicians, charity representatives and people with ME. She directed the workshops and people with ME actively participated in the discussions. The last workshop examined ME research and under‐served groups. The workshop was chaired by the third author and attended by the second author. The first author conceived the article and wrote it in consultation with the second and third authors.